2016
DOI: 10.2217/pmt-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Management of Fibromyalgia Syndrome in 2016

Abstract: Fibromyalgia syndrome is a chronic pain disorder and defies definitively efficacious therapy. In this review, we summarize the results from the early treatment research as well as recent research evaluating the pharmacological, interventional and nonpharmacological therapies. We further discuss future directions of fibromyalgia syndrome management; we specifically focus on the issues that are associated with currently available treatments, such as the need for personalized approach, new technologically oriente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 180 publications
2
42
0
3
Order By: Relevance
“…In the neural tissue, reduced GSH is present in abundance, which has been recognized as a cellular nonprotein thiol as it shields neural cells from the damaging effect of free radicals (67). GSH serves as an important antioxidant via its ROS scavenging potential (14,68). It has been reported that reserpine depletes monoamines via autoxidation of DA through inhibition of vesicular monoamine transportation or storage (11,28,69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the neural tissue, reduced GSH is present in abundance, which has been recognized as a cellular nonprotein thiol as it shields neural cells from the damaging effect of free radicals (67). GSH serves as an important antioxidant via its ROS scavenging potential (14,68). It has been reported that reserpine depletes monoamines via autoxidation of DA through inhibition of vesicular monoamine transportation or storage (11,28,69).…”
Section: Discussionmentioning
confidence: 99%
“…However, pregabalin produces only partial relief and does not cure FM (74). In the past few decades, medicines of herbal origin, including Rhizoma drynariae (75) and Baishao zongdai (68), demonstrated significant efficacy in terms of safety in the management of FM. Fisetin, a flavonoid polyphenol phytoconstituent, also showed promising potential for the clinical management of colorectal cancer (76).…”
Section: Discussionmentioning
confidence: 99%
“…The current evidence suggest for FM management antidepressants, cardiovascular exercise, and cognitive behavioral therapy [7]. Meta-analysis results agree that the medication approved by FDA-milnacipran-and duloxetine are effective in FM while there are concerns that the results showed only a moderate effect on pain and sleep, and no impact on fatigue [8].…”
Section: Fibromyalgiamentioning
confidence: 76%
“…There should be no uncertainty about one opioidnamely, tramadol-which has been used with moderate success in FM. 5 There have been no good double-blind long-term randomized trials of opioids in FM. In view of current concerns with respect to the harmful effects of such medications when used for the treatment of chronic non-cancer pain, such a trial for FM is unlikely in the foreseeable future.…”
Section: The Finalistsmentioning
confidence: 99%
“…4 To date its treatment has been only modestly successful. 4,5 The article by Fitzcharles et al 3 illustrates the difficulties in reaching a useful and clear agreement between patients and health care professionals for a treatment research agenda. The work, the time, and the number of people involved in this project were considerable, but the validity and originality of the results presented appear questionable.…”
Section: Introductionmentioning
confidence: 99%